Anisotropy function of a new 192-Ir brachytherapy source (Brazilian Journal of Radiation Sciences, 2021)
Brachytherapy is a type of radiotherapy that uses radioactive sources (seeds, wires, among others) close to the tumor. Is important to provide a detailed description of seed dosimetry, so only the tumor will be irradiated avoiding unnecessary dose on adjacent organs and structures. To evaluate the dosimetric parameter of the anisotropy function for a new brachytherapy source, this work proposes the use of microcube TLD-100 dosimeters to find the dose rate using the AAPM Task Group 43 protocol (TG-43). The anisotropy function represents dose distribution around the source and has a major role for characterization of a new iridium source being implemented in Brazil. The value of D(r,θ) was measured using Solid Water phantoms, r value being the distance from the geometric center of the source to the position of the dosimeter on the phantom, and θ being the angle formed between the longitudinal axis of the source and the line connecting the geometric center to the TLD. Monte Carlo calculations were performed to evaluate the anisotropy function to validate the experimental measurements. For each distance value (r), an anisotropy function was plotted (1.0, 2.0, 3.0, 4.0, 5.0, and 10.0 cm). The results obtained with Monte Carlo calculations agreed ±2% with the experimental values for r greater than 3.0 cm, so these results show a good distribution of dose around the seed considering the high energy of 192-Ir (average of 380 KeV) and encapsulation thickness.